DEDIFFERENTIATED LEIOMYOSARCOMA - Putri, Anggie Sasmita Kharisma (Oceana Biomedicina Journal, 2024)
ABSTRACTBACKGROUND : Leiomyosarcoma (LMS) is an aggressive soft tissue sarcoma that ranges from 7-10% of all cases of soft tissue sarcoma, usually occurring in adult and elderly patients.CASE REPORT : Patient Mr. M, male, 71 years old, construction worker, Tulungagung Regency. The patient has a main complaint, namely a lump under the right armpit, felt since 2 months before visiting dr. Iskak Tulungagung.DISCUSSION : Pleomorphic LMS or dedifferentiated LMS shows nonspecific and poorly differentiated pleomorphism. To make this diagnosis, the characteristic morphological features of classic LMS must be obtained, or the patient must have a prior history of LMS. On immunohistochemistry, approximately 50–75% of pleomorphic LMS are positive for at least one myogenic marker, although the smear is often weaker and more focal than in a typical area of leiomyosarcoma.CONCLUSION: Microscopically, the morphological appearance of dedifferentiated LMS can resemble the appearance of other high-grade sarcomas, so clinical, radiological, histopathological considerations and further examinations such as immunohistochemical smears are needed.